Clinical and prognostic significance of Merkel cell polyomavirus in nonsmall cell lung cancer. Issue 3 (January 2017) - Kim, Gun-Jik; Lee, Jae-Ho; Lee, Deok Heon
Abstract : Abstract: Recently, an association between Merkel cell polyomavirus (MCPyV) and epidermal growth factor receptor (EGFR) mutations in nonsmall cell lung cancer (NSCLC) was reported. However, the underlying carcinogenic effects and the prognosis related to MCPyV are still unclear. The aim of this study was to clarify the incidence and prognosis related to MCPyV infections in NSCLC. Tissue samples from 167 NSCLC patients (92 with squamous cell carcinomas [SCCs] and 75 with adenocarcinomas) were analyzed for the presence of MCPyV and EGFR mutations. Clinicopathological characteristics, disease-free survival rate, and overall survival rate were assessed with respect to MCPyV. MCPyV DNA was detected in 30 patients (18.0%) out of 167 patients, and EGFR mutations were found in 31 out of 127 patients (24.4%). EGFR mutations were more frequently detected in MCPyV-positive patients than in MCPyV-negative patients; however, this did not reach statistical significance ( P = 0.075). There was no difference in overall survival between patients with and without MCPyV infections. The disease-free survival rate of patients with pN0 stage, SCC, or EGFR mutations was lower for patients with MCPyV than without MCPyV ( P = 0.036, 0.042, and 0.050, respectively). Although the prevalence of MCPyV infection was relatively low, the presence of MCPyV DNA was significantly correlated with cancer prognosis in subgroups of NSCLC patients. These results suggest that MCPyV may be partly associated with pathogenesis and prognosis in some cases of NSCLC.